Notes on Quercus salicifolia and description of a new species of Quercus section Lobatae (Fagaceae) from Mexico - Valencia-A, Susana; Soto-Arellano, Oscar Javier (Phytotaxa, 2025)
The synonymy of Quercus salicifolia is reviewed and an amended description that allows its recognition is presented. The main characteristics that separate Q. salicifolia from species that have been recently proposed as its synonyms are presented. Additionally, Q. salasiae is proposed as a new species of the section Lobatae. It is compared with Q. salicifolia and Q. nixoniana, with which it presents morphological similarity.